Cellular response in three-dimensional spheroids and tissues exposed to real and simulated microgravity: a narrative review - Daan W. A. van den Nieuwenhof; Lorenzo Moroni; Joshua Chou; Jochen Hinkelbein (npj Microgravity)
Abstract The rising aging population underscores the need for advances in tissue engineering and regenerative medicine. Alterations in cellular response in microgravity might be pivotal in unraveling the intricate cellular mechanisms governing tissue and organ regeneration. Microgravity could improve multicellular spheroid, tissue, and organ formation. This review summarizes microgravity-induced cellular alterations and highlights the potential of tissue engineering in microgravity for future breakthroughs in space travel, transplantation, drug testing, and personalized medicine.